2021
DOI: 10.1111/cpf.12694
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between carotid and coronary calcification in patients with coronary artery disease

Abstract: Background Atherosclerosis is a multi‐system pathology with heterogeneous involvement. We aimed to investigate the relationship between the presence and severity of carotid and coronary calcification in a group of patients with coronary artery disease. Methods Sixty‐three patients presenting with unstable angina or positive stress test for myocardial ischaemia were enrolled in this study. All patients underwent CT scanning of the carotid and coronary arteries using the conventional protocol and Agatston scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…It should be noted that the evaluation of calcium in carotid arteries was performed by Gepner at al. using ultrasound instead of CT. More encouraging data corroborating our findings were achieved by Shenouda et al in 2021, who reported the results of a retrospective study carried out on 63 patients with unstable angina or positive stress test for myocardial ischaemia [25]. In these patients, the overall CACs showed a significant correlation with total carotid score (rho = 0.34, p = 0.007), particularly with the left carotid score (rho = 0.38, p = 0.002), while the correlation with the right carotid score was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that the evaluation of calcium in carotid arteries was performed by Gepner at al. using ultrasound instead of CT. More encouraging data corroborating our findings were achieved by Shenouda et al in 2021, who reported the results of a retrospective study carried out on 63 patients with unstable angina or positive stress test for myocardial ischaemia [25]. In these patients, the overall CACs showed a significant correlation with total carotid score (rho = 0.34, p = 0.007), particularly with the left carotid score (rho = 0.38, p = 0.002), while the correlation with the right carotid score was not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…The heterogeneity of VC can be easily appreciated from the arterial segments involved and inter-individual variations in severity. Studies have revealed that the prevalence of arterial calcification varies depending on the arterial segments, and a small-scale study showed that in the same group of older patients, carotid and coronary calcifications were present in 53.4% and nearly 100% of participants, respectively [25]. The distribution of calcification severity also tended to be more severe for coronary calcification, whose calcification scores could reach 10-fold higher than those for carotid calcification [25].…”
Section: Through the Lens Of Vc Morphological Diversitymentioning
confidence: 98%
“…Human data showed that different arterial segments reacted differently with regard to their calcification susceptibility to air pollution, and a meta-analysis showed that fine particulate matter exposure correlated more closely with carotid arteriopathy than with coronary calcification [74]. The degree of coronary calcification was significantly associated with carotid calcification, but with side deviations (left > right) [25]. Interestingly, hypertension correlated with higher carotid calcification scores, whereas diabetes and dyslipidemia correlated with higher coronary calcification scores.…”
Section: Clinical Manifestations and Risk Correlates Based On The Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is common in patients with coronary and peripheral artery diseases. 2 Cerebrovascular events due to carotid artery diseases are common in developed countries. 3 In clinical practice, imaging obtained using carotid duplex ultrasound (USG) is important in both the management of patients with acute stroke and the risk assessment of coronary artery disease or stroke.…”
Section: Introductionmentioning
confidence: 99%